2004
DOI: 10.1111/j.1471-4159.2004.02536.x
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric potential of the M2 muscarinic cholinergic receptor

Abstract: G protein-coupled receptors are known to exist as oligomers. Although such aggregates often are referred to as dimers, there is little direct evidence regarding their oligomeric size. In the present investigation, c-Myc-, FLAG-, and influenza hemagglutinin (HA)-tagged forms of the M 2 muscarinic receptor have been coexpressed in Sf9 cells to probe for aggregates larger than a dimer. Immunochromatography, immunoprecipitation, and immunoblotting were carried out with various combinations of antibodies directed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 47 publications
3
43
0
Order By: Relevance
“…The data indicate that the receptor exists as a tetramer, as suggested previously on the basis of electrophoretic mobility (4,5,18), copurification (4,5,18), and noncompetitive effects in the binding of agonists and antagonists (4, 18 -20). Similar studies on other GPCRs can be expected to reveal the degree of oligomeric diversity within the rhodopsin-like subgroup and across the family at large.…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…The data indicate that the receptor exists as a tetramer, as suggested previously on the basis of electrophoretic mobility (4,5,18), copurification (4,5,18), and noncompetitive effects in the binding of agonists and antagonists (4, 18 -20). Similar studies on other GPCRs can be expected to reveal the degree of oligomeric diversity within the rhodopsin-like subgroup and across the family at large.…”
mentioning
confidence: 51%
“…4), but the composition of the bands may be unclear, and the size under the conditions of electrophoresis may have little in common with that in the membrane. Larger oligomers also have been identified by approaches in which detection requires the colocalization of three or four proteins, each bearing a different tag (5)(6)(7)(8)(9)(10)(11), but such procedures place only a lower limit on the possible size of the array.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By combining BiFC and BiLC with BRET measurements, we now showed that heteromeric complexes between BILF1 and CXCR4 consist of at least four interacting GPCR proteins at the same time. Such oligomeric organization has been observed for native rhodopsin in disc membranes of rod outer segments by using atomic force microscopy (11) but have also been observed between class C GPCRs GABA B1 and GABA B2 (36) and between various class A GPCRs using various modifications and/or combinations of resonance energy transfer-based methods as well as cross-linking experiments (22,(37)(38)(39)(40)(41). Hitherto, however, the functional significance and/or necessity of oligomeric receptor complexes versus receptor dimers have remained puzzling.…”
Section: Discussionmentioning
confidence: 99%
“…Trimeric receptor complexes have been indeed identified (Gandia et al, 2008). They include the A 2A -D 2 -mGlu 5 (Cabello et al, 2009) heteroreceptor complex, the muscarinic M 2 homotrimer (Park and Wells, 2004), the dynamic Gal 1 -5-HT 1A -GPR 39 heterotrimer (Tena-Campos et al, 2015), and the putative Gal 1 -Gal 2 -5-HT 1A heterotrimer (Millón et al, 2016). Tetrameric assemblies of β 2 -adrenergic receptors were demonstrated by the group of Kobilka to occur spontaneously following reconstitution into phospholipid vesicles (Fung et al, 2009), suggesting that β 2 -adrenergic receptor oligomerization is an intrinsic property of the receptor.…”
Section: Quaternary Structure Of Gpcr Complexesmentioning
confidence: 99%